Changing attitudes to Europe: British teacher education and the European dimension - Convery, Anne (2002)
This thesis examines the attitudes to Europe of student teachers during their initial training course, in order to investigate their development in relation to the European dimension in both the teacher education and school curricula. After setting the current political context, the historical and educational background to the study is outlined, together with a personal rationale for the research. A close scrutiny of the literature pertaining to Europe and the European dimension enabled a conceptual framework of key terms to be established. Consideration of a range of theoretical perspectives in the field of cognitive psychology led to the choice of Bronfenbrenner's Ecology of Human Development as an appropriate framework within which to examine the specific research questions. His belief in human development focuses on the complex interactions between an individual and the environments in which s/he is situated. The individual is interpreted in this study as the student teacher, who develops in a series of ever-widening environments (local, national and European). The research is based on a mixed-model paradigm, drawing on both quantitative and qualitative methods in order to best address the research questions. Data collection took place in two phases: a major four year UK-based study; and a European survey in six EU countries. The research tools used were pre- and post-course questionnaires and semi-structured interviews, which generated large amounts of rich quantitative and qualitative data. An in-depth and detailed analysis of the data resulted in the emergence of a number of key findings. These are discussed and interpreted in the light of the theoretical framework, leading to theoretical and conceptual refinement. Finally, recommendations are made concerning implications for future policy and practice, in terms of European education policy, research, teacher education and schools.